Caregiver awareness of cerebrovascular risk of patients with dementia due to Alzheimer's disease in São Paulo, Brazil (Archives of Clinical Psychiatry, 2014)
Background Proper control of cerebrovascular risk is essential to prevent cognitive change in dementia due to Alzheimer’s disease (AD). Objective To investigate whether caregiver awareness to control cerebrovascular risk impacts the lifestyles of patients with AD. Methods Consecutive outpatients with AD were assessed for demographic features, Clinical Dementia Rating scores, cerebrovascular risk, pharmacotherapy, dietary therapy and practice of physical activities. Patients and caregivers were inquired on awareness of the importance of measures to control cerebrovascular risk. Chi-square test was employed for statistics, significance at ρ < 0.05. Results A total of 217 patients were included; whereas 149 caregivers (68.7%) were aware of the need to control cerebrovascular risk, only 11 patients (5.1%) simultaneously practiced physical activities and received pharmacological treatment and dietary therapy. Patients with hypertension and diabetes mellitus were more likely to receive dietary therapy (ρ = 0.007). Male patients were more engaged in physical activities (ρ = 0.018). Patients in earlier AD stages exercised (ρ = 0.0003) and received pharmacological treatment more often (ρ = 0.0072). Caregiver awareness of the need to control cerebrovascular risk was higher when patients had hypertension (ρ = 0.024) and/or hypercholesterolemia (ρ = 0.006), and influenced adherence to dietary therapy (ρ = 0.002) and to pharmacological treatment (ρ = 0.001). Discussion Caregiver awareness of the need to control cerebrovascular risk has positive impacts for patients with AD.